Contribution of water rejuvenation induced by climate warming to evapotranspiration in a Siberian boreal forest - Park, Hotaek; Hiyama, Tetsuya; Suzuki, Kazuyoshi (Frontiers in Earth Science, 2022)
Water age is a useful metric to evaluate the influence of anthropogenic and natural forcings on the terrestrial water cycle. Current climate warming is enhancing the warming of permafrost soil in the Arctic. Although permafrost is a crucial component of the Arctic terrestrial water cycle, its influence on processes regulating the fluxes and ages of Arctic terrestrial water, particularly soil storage and evapotranspiration, is not well understood. In this study, a water age calculation scheme was implemented into the coupled hydrological and biogeochemical model (CHANGE) to assess the mechanisms through which climate warming affects the soil water storage–evapotranspiration flux–water age feedback cycle in a boreal forest. Continuous air temperature increase from 1980–2016 caused earlier snowmelt and soil thawing, inducing decreasing age trends in snow- and rain-sourced water. The younger water contributed to higher spring evapotranspiration. In summer, the higher evapotranspiration fluxes dried the surface soil layer. In turn, the drier surface layer increased the loss of fresh rainwater. Autumn precipitation, preserved in the frozen winter soil until the following spring, became an additional source of water and enhanced plant transpiration in the following summer. This increase accounted for 4.2% of the annual total transpiration. These results suggest that permafrost warming, characterized by earlier soil thawing and later freezing, induced higher evapotranspiration fluxes, thereby shortening the residence time of precipitation-sourced water in the active layer and further rejuvenating water in soil layers and in evapotranspiration fluxes. Under future climate warming conditions, this effect is expected to intensify and the water cycle will accelerate.